Effect of niobium oxide (Nb2O5) addition to the physical and mechanical properties of cold isostatic press zirconia toughened alumina (ZTA) - Nurul Khairunnisa, Su (Universiti Malaysia Perlis (UniMAP), 2018)
Master of Science in Materials Engineering